Epidemiology and Genetic Diversity of Bartonella in Rodents in Urban Areas of Guangzhou, Southern China - Yao, Xin-Yan; Liu, Hong; Sun, Jing; Zhang, Yu-Qian; Lv, Zhi-Hang; Zhang, Xue-Lian; Shao, Jian-Wei (Frontiers in Microbiology, 2022)
Bartonella spp. are gram-negative bacteria that can infect a wide range of mammals and transmitted by various blood-sucking arthropods. Rodents are considered to be natural reservoir of many Bartonella species, including those zoonotic species. The close contact between rodent and human in urban environments increase the chance of rodent-borne pathogens including Bartonella, transmit to humans. Investigation on the epidemiological characteristics of Bartonella infection in rodents is of great significance for the prevention and control of human Bartonellosis. In this study, rodents were captured to investigate the prevalence of Bartonella in urban areas of Guangzhou city. Six official or candidate species of Bartonella including two confirmed zoonotic species were detected with an overall prevalence of 6.4% in rodents captured herein. In addition, Rattus norvegicus was the predominant host species for Bartonella infection, and B. queenslandensis was the dominant species circulating in rodents in these areas. These results provide insights into the prevalence and genetic diversity of Bartonella species circulating in rodent in urban areas of Guangzhou, and also remind that much more attentions should be paid to the surveillance of rodent-associated Bartonella species in these areas.